Macromol. Mater. Eng. 11/2017. Issue 11 (17th November 2017) - Erdem, Talha; Idris, Muazzam; Demir, Hilmi Volkan; Tuncel, Dönüs
Abstract : Front Cover : Cucurbit[7]uril‐based conjugated polyrotaxanes are synthesized and co‐crystallized with sugar‐based matrices such as sucrose and trehalose to obtain highly efficient color‐converting solids with remarkably high QYs (>50%) which are suitable for solid‐state lighting. This is reported by Talha Erdem, Muazzam Idris, Hilmi Volkan Demir and Dönüs Tuncel, in article number1700290 .